Farm and Companion Animal Organoid Models in Translational Research: A Powerful Tool to Bridge the Gap Between Mice and Humans - Kawasaki, Minae; Goyama, Takashi; Tachibana, Yurika; Nagao, Itsuma; Ambrosini, Yoko M. (Frontiers in Medical Technology, 2022)
Animal organoid models derived from farm and companion animals have great potential to contribute to human health as a One Health initiative, which recognize a close inter-relationship among humans, animals and their shared environment and adopt multi-and trans-disciplinary approaches to optimize health outcomes. With recent advances in organoid technology, studies on farm and companion animal organoids have gained more attention in various fields including veterinary medicine, translational medicine and biomedical research. Not only is this because three-dimensional organoids possess unique characteristics from traditional two-dimensional cell cultures including their self-organizing and self-renewing properties and high structural and functional similarities to the originating tissue, but also because relative to conventional genetically modified or artificially induced murine models, companion animal organoids can provide an excellent model for spontaneously occurring diseases which resemble human diseases. These features of companion animal organoids offer a paradigm-shifting approach in biomedical research and improve translatability of in vitro studies to subsequent in vivo studies with spontaneously diseased animals while reducing the use of conventional animal models prior to human clinical trials. Farm animal organoids also could play an important role in investigations of the pathophysiology of zoonotic and reproductive diseases by contributing to public health and improving agricultural production. Here, we discuss a brief history of organoids and the most recent updates on farm and companion animal organoids, followed by discussion on their potential in public health, food security, and comparative medicine as One Health initiatives. We highlight recent evolution in the culturing of organoids and their integration with organ-on-a-chip systems to overcome current limitations in in vitro studies. We envision multidisciplinary work integrating organoid culture and organ-on-a-chip technology can contribute to improving both human and animal health.